2009
DOI: 10.1039/b916507j
|View full text |Cite
|
Sign up to set email alerts
|

Low activation energy dehydrogenation of aqueous formic acid on platinum–ruthenium–bismuth oxide at near ambient temperature and pressure

Abstract: Highly selective dehydrogenation of formic acid in water was observed at near ambient temperature on a metal/metal oxide catalyst composed of platinum ruthenium and bismuth with a low activation energy of 37.3 kJ mol(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…18 The initial turnover frequency [TOF, Eq. (S1)] over Co 0.30 Au 0.35 Pd 0.35 /C is measured to be 80 h −1 at 298 K. To the best of our knowledge, this initial TOF value is the highest value ever reported for FA decomposition using a heterogeneous catalyst without any additive at room temperature,6e and is even comparable to most of those with additives or at elevated temperatures 7ac,g,i. Furthermore, the decomposition of FA can be almost completed within 600 minutes [91 % of conversion, Eq.…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…18 The initial turnover frequency [TOF, Eq. (S1)] over Co 0.30 Au 0.35 Pd 0.35 /C is measured to be 80 h −1 at 298 K. To the best of our knowledge, this initial TOF value is the highest value ever reported for FA decomposition using a heterogeneous catalyst without any additive at room temperature,6e and is even comparable to most of those with additives or at elevated temperatures 7ac,g,i. Furthermore, the decomposition of FA can be almost completed within 600 minutes [91 % of conversion, Eq.…”
Section: Methodsmentioning
confidence: 69%
“…6 Recently, much progress has been made on the heterogeneous catalysis for the selective dehydrogenation of FA 6c–e. 7 However, the thermodynamic and kinetic properties of FA dehydrogenation, especially without any extra additive,6e, 7c still need to be further promoted 6c–e. 7, 8 More importantly, all the reported heterogeneous catalysts up to now only consist of noble metals, including, for example, Pd, Au, Ag, and Pt,6c–e, 7, 8 which greatly hinders their large‐scale practical applications because of their high costs and low reserves in the earth’s crust.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain ultrapure H 2 , FA dehydration must be avoided and, therefore, the optimum catalyst should not only display high catalytic ability under mild conditions, but it should also be selective toward the FA dehydrogenation pathway. It was reported that the active systems are mainly based on precious metals such as Ir, Ru, Au, Pt, and Pd . Among these precious metal catalysts, Pd‐based heterogeneous catalysts have been found to be the most active single‐component nanocatalysts and have provided notable activities in the additive‐free FA dehydrogenation at low temperature .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, a number of research efforts have been devoted to the study of effective catalysts for HCOOH dehydrogenation in which noble metals are usually used, such as Pt [23,24] Pd [25] and Rh [26]. Recent studies showed that highly pure hydrogen without CO could be obtained from HCOOH over soluble organometallic complexes [22,23,27] or insoluble heterogeneous catalysts [28][29][30] in aqueous solution at ambient temperatures. Tedsree et al [31] indicated that Ag nanoparticles coated with a thin layer of Pd atoms can considerably enhance hydrogen production from formic acid at room temperature.…”
Section: Introductionmentioning
confidence: 99%